International research on the civic engagement of the youth and adolescents. Young citizens in the digital age - María Carmen Robles Vílchez (Revista Electrónica Interuniversitaria de Formación del Profesorado)
This article presents a review of some of the research in the international context aimed at unveiling and valuing the experience of young people in experiences and beliefs regarding citizenship (Burke, 2007). Such research is generally intended to obtain information on students’ knowledge, attitudes and civic behavior in their own schools. We will highlight throughout the present paper that previous studies and the current state of scientific knowledge in civic education focuses on purely formal and structural aspects and lack a deep understanding and interpretation of the experiences of young citizens. We conclude, after our review, that it is necessary to include more comprehensive factors in the research and enquiry into the experiences and civic training of the youth.